Potential genotoxicity impacts of a co-exposure of polypropylene microplastic and antibiotics to freshwater pearl mussel Hyriopsis cumingii (Lea, 1852) - Nguyen, Ngoc Tuan; Nguyen, Danh Thien; Pham, Gia Minh Tu; Mai, Huong (Vietnam Journal of Science and Technology, 2025)
Microplastics (MPs) are becoming ubiquitous, and their environmental fate is becoming an issue concern. MPs can adsorb antibiotics to coexist and accumulate in the aquatic environment in the form of complexes, resulting in unforeseeable adverse consequences. Herein, we investigated the genotoxic effects of coexist of polypropylene (PP) microplastic and two antibiotics of sulfamethoxazole (SMX) and oxytetracycline (OTC) at environmental concentrations on gill and gastrointestinal tract (GIT) cells of freshwater pearl mussel Hyriopsis cumingii. Results showed that coexist of PP and antibiotics SMX and OTC at environmental concentrations can cause the DNA damage (5.0 – 8.7% in gill and 4.5 7.9 % in GIT) and micronucleus (10.8 – 20.9 ‰ in gill and 11.9 – 18.6 ‰ in GIT) for H. cumingii. By principal component analysis, we found that there was a strong relationship between microplastic accumulation in the GIT and biomarkers, including DNA damage and micronucleus, for H. cumingii co-exposed to PP microplatics in combination with only OTC antibiotic. Meanwhile, only a strong correlation was detected between microplatic accumulation in gill or GIT and DNA damage in those tisues, when H. cumingii was exposed to mixing anibiotics OTC and SMX along with PP microplastic. Our study contributed to improve the understanding of the adverse genetic impacts of coexistance of PP microplastics and antibiotics (SMX and OTC) in the environment as well as to provided essential information for ecological risk assessment of MPs and antibiotics pollution.